BiOBr oyster shell composite photocatalyst as well as preparation method and application thereof

Through the preparation of the composite photocatalyst of BiOBr and oyster shell, the separation of photogenerated carriers is accelerated by using the oyster shell as a carrier material, and the problem of low photoenergy utilization rate of BiOBr photocatalyst and fast photogenerated carrier recombination is solved, and water pollution is achieved The efficient degradation and stability of the substance are improved.

CN119259092APending Publication Date: 2025-01-07FIRST INSTITUTE OF OCEANOGRAPHY MNR
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411387900.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The problem of BiOBr photocatalysts in low light energy utilization and fast photogenerated carrier recombination has limited its application in water pollution treatment, and a method to improve its photocatalytic activity and stability is needed.

Method used

The photocatalyst composite photocatalyst with BiOBr and oyster shell was prepared by ultrasonic dispersion and high-temperature reaction. The molar ratio of BiOBr and oyster shell was 0.5-2:1. The oyster shell was used as a support material to accelerate the separation of photogenerated carriers and improve photocatalysis. performance.

Benefits of technology

The efficient photocatalytic activity and stability of the BiOBr/oyster shell composite photocatalyst under visible light is achieved, and the efficient degradation effect on organic dyes and antibiotic pollutants in water bodies is achieved, which significantly improves the photocatalytic performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259092A_ABST
    Figure CN119259092A_ABST
Patent Text Reader

Abstract

The invention discloses a BiOBr oyster shell composite photocatalyst as well as a preparation method and application thereof. The composite photocatalyst is prepared by taking oyster shell as a carrier, loading a BiOBr material on the oyster shell carrier, converting the oyster shell into an oyster shell functional material, and then adding KI and Bi (NO3) 3 by a solvothermal method to generate the BiOBr / oyster shell composite photocatalyst in situ. The BiOBr / oyster shell composite photocatalyst with visible-light response is constructed, the oyster shell serves as a carrier material, the specific surface area of BiOBr is increased, meanwhile, photon-generated carrier separation can be accelerated, the composite material is endowed with efficient photocatalytic activity and adsorbability under visible light, the efficient degradation effect on dye and antibiotic pollutants in water is achieved, and the visible-light response BiOBr / oyster shell composite photocatalyst has a good application prospect. While resource reutilization of the oyster shells is realized, the method has good practical value and potential application prospect in the fields of water purification and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmentally friendly material preparation, and specifically relates to a BiOBr oyster shell composite photocatalyst and a preparation method and application thereof. Background Art

[0002] In recent years, the pollution of aquatic environments by different categories of organic pollutants has attracted worldwide attention. The toxicity and carcinogenicity of synthetic dyes and the persistence of antibiotic resistance genes in the environment may pose a threat to the balance of the entire ecosystem, including precious human life. Photocatalysis is considered to be an environmentally friendly, low-cost technology that can completely destroy most organic pollutants with the help of endless solar energy. In photocatalytic reactions, the choice of catalyst is crucial, and the type and performance of photocatalytic materials directly affect the efficiency and selectivity of the reaction. In order to overcome the problem of photocatalysis and its small scope of use, researchers are constantly exploring new visible light-driven photocatalytic materials. Bismuth-based photocatalysts have attracted much attention due to their low toxicity, low cost and high stability. Bismuth-based semiconductor materials that have been reported include binary oxides or sulfides (such as Bi 2 O 3 、Bi 2 S 3 ), multi-component oxides (such as BiVO 4 、Bi 2 MoO 6 and Bi 2 WO 6 ) and oxyhalides (such as BiOX, where X = Cl, Br and I), etc., have shown potential application value in water treatment, air purification, photocatalytic removal of organic pollutants and other fields.

[0003] Among them, BiOBr is well known for its square Matlockite structure, the lattice is composed of [Bi 2 O 2 ] 2+ Layer sandwiched between double [Br - ] layers, forming [Br-Bi-O-Bi-Br] sheets, which are bonded by stacking along the (001) direction. This unique structure type is said to be able to 2 O 2 ] 2+ and double [Br - ] along the (001) direction, which helps to effectively separate the photoelectron-hole pairs, suggesting that BiOBr has great potential in utilizing solar energy for visible light catalytic applications. However, BiOBr also faces problems such as low light energy utilization and fast recombination of photogenerated carriers, which have become bottlenecks restricting its development and application. Therefore, it is increasingly necessary to explore simple and reliable synthesis methods for BiOBr photocatalysts with better physical and chemical properties and higher photocatalytic activity.

[0004] At present, doping, heterostructure construction, surface modification and carrier loading have been developed and applied to improve the photocatalytic activity of BiOBr. 3 Under mediated conditions, the (110) exposed BiOBr nanosheets synthesized under neutral conditions can achieve rapid charge transfer and thus have efficient photocatalytic performance. 3 The porous biochar skeleton has good electrical conductivity and can be used as a low-cost and efficient carrier material to reduce the rapid recombination of electrons and electron holes in the photocatalytic process, enhance the photocatalytic efficiency, and rapidly degrade organic pollutants. It has broad application prospects in solving water pollution. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a BiOBr / oyster shell composite photocatalyst and its preparation method and application in view of the deficiencies in the prior art. The BiOBr / oyster shell composite photocatalyst of the present invention has high efficient photocatalytic activity and stability under visible light, and has a high efficient degradation effect on organic dyes and antibiotic pollutants in water bodies.

[0006] The BiOBr / oyster shell composite photocatalyst provided by the present invention comprises raw materials for preparation thereof including BiOBr and oyster shell, wherein the molar ratio of BiOBr to oyster shell is 0.5-2:1.

[0007] The preparation method of the BiOBr / oyster shell composite photocatalyst comprises the following steps:

[0008] 1) Preparation of oyster shell powder

[0009] Taking discarded oyster shells as raw materials, washing, calcining and grinding them to obtain oyster shell powder raw materials;

[0010] 2) Preparation of BiOBr / oyster shell composite photocatalyst

[0011] Bismuth nitrate pentahydrate Bi(NO 3 ) 3 ·5H 2O is added to anhydrous ethanol and ultrasonically dispersed to obtain dispersion A1; potassium bromide KBr is then added to anhydrous ethanol and ultrasonically dispersed to obtain dispersion A2; dispersion A2 is then added dropwise to dispersion A1, and stirring is continued after the dropwise addition is completed to obtain a mixed solution A3, oyster shell powder is added to the mixed solution A3, and ultrasonic stirring is performed again to mix evenly to obtain a mixed solution A4, the mixed solution A4 is subjected to a high-temperature reaction, cooled to room temperature after the reaction, and centrifuged, washed and dried to obtain a BiOBr / oyster shell composite photocatalyst.

[0012] In step 1), the grinding speed is 500 r / min and the grinding time is 1 h; the calcination condition is to increase the temperature to 700°C at a heating rate of 5°C / min and calcine for 3 to 6 hours.

[0013] In the ultrasonic dispersion in step (2), the ultrasonic frequency is 200W and the ultrasonic dispersion time is 0.5h; the dispersion A2 is added dropwise to the suspension A1, and after the dropwise addition is completed, stirring is continued for 0.5h to obtain the mixed solution A3, and the stirring speed is 1000r / min.

[0014] As a preferred embodiment, the Bi(NO 3 ) 3 ·5H 2 The molar ratio of O and KBr is 1:1.

[0015] The molar ratio of BiOBr to oyster shell powder is 0.5-2:1.

[0016] In the step 2), the mixed solution A4 is transferred to a high-pressure reactor equipped with a polytetrafluoroethylene liner, and then the reactor is placed in an electric constant temperature blast drying oven and heat treated at 180° C. for 12 to 24 hours; after the reaction is completed, the reactor is cooled to room temperature, and the BiOBr / oyster shell composite photocatalyst is obtained by suction filtration, washing and drying.

[0017] The invention also provides application of the BiOBr / oyster shell composite photocatalyst in degrading dyes and antibiotics.

[0018] Compared with the existing technology, it has the following characteristics:

[0019] (1) The BiOBr / oyster shell composite photocatalyst prepared by a simple solvent thermal synthesis method has good visible light absorption performance and photocatalytic performance, can efficiently degrade dyes and antibiotics, and has better photocatalytic activity than BiOBr monomer materials;

[0020] (2) The BiOBr / oyster shell composite photocatalyst prepared by the present invention has good stability and reusability;

[0021] (3) The BiOBr / oyster shell composite photocatalyst prepared by the present invention uses oyster shell as a carrier material, which can accelerate the separation of photogenerated carriers and improve the visible light catalytic activity. It has good practical value and potential application prospects in the fields of water purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : XRD patterns of the samples prepared in Example 1 of the present invention and Comparative Example 1, wherein the abscissa is 2θ (angle), the unit is degree; the ordinate is Intensity, the unit is au (absolute unit);

[0023] Figure 2-a : Field emission scanning electron microscope (FESEM) photo of the oyster shell powder prepared in Example 1 of the present invention;

[0024] Figure 2-b : Field emission scanning electron microscope (FESEM) photo of the BiOBr monomer material prepared in Comparative Example 1 of the present invention;

[0025] Figure 2-c : Field emission scanning electron microscope (FESEM) photo of the composite material prepared in Example 1 of the present invention;

[0026] Figure 3 : The concentration of the dye methylene blue (MB) changes with time in the photocatalytic degradation reaction of the sample prepared in Example 1 of the present invention, wherein the abscissa is Time (time), the unit is min (minutes), and the ordinate is C t / C 0 , C 0 is the initial concentration of MB before the reaction, C t is the MB concentration at reaction time t (■ represents oyster shell, ● represents BiOBr, ▲ represents BiOBr / oyster shell);

[0027] Figure 4 : The concentration variation curve of MB, dye malachite green (MG), and antibiotic ciprofloxacin (CIP) over time in the photocatalytic degradation reaction of the sample prepared in Example 1 of the present invention, wherein the abscissa is Time, the unit is min, and the ordinate is C t / C 0 , C 0 is the initial concentration of MB before the reaction, C t is the pollutant concentration at reaction time t (■ represents MB, ● represents CIP, ▲ represents MG); DETAILED DESCRIPTION

[0028] The specific implementation of the technical solution of the present invention is described in detail below, but the present invention is not limited to the following description:

[0029] The present invention compounds BiOBr and oyster shells to construct a composite material with oyster shells as carriers, thereby accelerating the separation of photogenerated carriers on the surface of the composite material, thereby improving the photocatalytic performance, which is of great significance to the practical application of BiOBr in the field of photocatalysis and the recycling of oyster shells.

[0030] The present invention is described in detail below with reference to specific embodiments and drawings.

[0031] Comparative Example 1:

[0032] The preparation of monomer BiOBr comprises the following steps:

[0033] 3 mmol of Bi(NO 3 ) 3 ·5H 2 O was added to 20 mL of anhydrous ethanol to obtain dispersion A1, 3 mmol of KI was added to 20 mL of anhydrous ethanol to obtain dispersion A2, and after ultrasonic dispersion at a frequency of 200 W for 0.5 h, dispersion 1 was added to dispersion A2 under continuous stirring, and stirring was continued at 1000 r / min for 0.5 h. The dispersion was transferred to a 50 mL polytetrafluoroethylene reactor and reacted at 180° C. for 24 h. After cooling to room temperature, the precipitate was collected by filtration, washed with deionized water and ethanol, and dried at 60° C. under normal pressure after washing to obtain a BiOBr monomer material, which was recorded as BiOBr.

[0034] Embodiment 1:

[0035] A BiOBr / oyster shell composite photocatalyst is prepared by the following preparation method:

[0036] (1) Preparation of oyster shell powder:

[0037] Take discarded oyster shells as raw materials, wash them with water and then dry them, grind them in a ball mill at 500r / min for 1h, then put them in a tubular furnace, heat them to 700°C at a heating rate of 5°C / min, and calcine them for 3h to obtain oyster shell powder raw materials.

[0038] (2) Preparation of BiOBr / oyster shell composite photocatalyst:

[0039] 3mmol Bi(NO 3 ) 3 ·5H 2O was added to 20 mL of anhydrous ethanol and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A1; 3 mmol KBr was then added to 20 mL of anhydrous ethanol to be completely dissolved and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A2; dispersion A2 was then added dropwise to dispersion A1, and after the addition was completed, stirring was continued at 1000 r / min for 0.5 h to obtain mixed solution A3, 3 mM oyster shell powder was added to the mixed solution A3, and ultrasonically dispersed at 200 W for 0.5 h again to obtain mixed solution A4, and the mixed solution A4 was transferred to a 50 mL polytetrafluoroethylene reactor, reacted at 180 ° C for 24 h, cooled to room temperature, filtered and collected the precipitate, washed with deionized water and ethanol, and dried at 60 ° C under normal pressure to obtain a BiOBr / oyster shell composite photocatalyst.

[0040] The XRD patterns of the samples obtained in Example 1 of the present invention and Comparative Example 1 are shown in Figure 1 ,Depend on Figure 1 It can be seen that all the diffraction peaks of pure BiOBr can be matched with BiOBr (PDF No.78-0348), indicating that it is of high purity and well crystallized. For pure oyster shell, these diffraction peaks can be matched with CaCO 3 (PDF No.88-1807). The spectrum of the BiOBr / oyster shell composite contains all the characteristic peaks of BiOBr and oyster shell. In addition, compared with pure BiOBr, the peak position of the BiOBr / oyster shell composite is almost unchanged, indicating that the loading of oyster shell has little effect on the lattice structure of BiOBr.

[0041] The FESEM photos of the samples obtained in Example 1 of the present invention and Comparative Example 1 are shown in Figure 2. As can be seen from Figure 2, the oyster shell is a sheet-like stacked structure. The morphology of pure BiOBr is a stacked two-dimensional nanosheet structure, showing a unique layered structure. The composite material is formed by in-situ growth of two-dimensional BiOBr nanosheets on the surface of the oyster shell, and the BiOBr nanosheets are evenly and vertically anchored on the surface of the oyster shell powder.

[0042] Embodiment 2:

[0043] A BiOBr / oyster shell composite photocatalyst, which is different from Example 1 in that the molar ratio of BiOBr to oyster shell is controlled to be 0.5:1, is prepared by the following preparation method:

[0044] (1) Preparation of oyster shell powder:

[0045] Take discarded oyster shells as raw materials, wash them with water and then dry them, grind them in a ball mill at 500r / min for 1h, then put them in a tubular furnace, heat them to 700°C at a heating rate of 5°C / min, and calcine them for 3h to obtain oyster shell powder raw materials.

[0046] (2) Preparation of BiOBr / oyster shell composite photocatalyst:

[0047] 3mmol Bi(NO 3 ) 3 ·5H 2 O was added to 20 mL of anhydrous ethanol and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A1; 3 mmol KBr was then added to 20 mL of anhydrous ethanol to be completely dissolved and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A2; dispersion A2 was then added dropwise to dispersion A1, and after the addition was completed, stirring was continued at 1000 r / min for 0.5 h to obtain mixed solution A3, 6 mM oyster shell powder was added to the mixed solution A3, and ultrasonically dispersed at 200 W for 0.5 h again to obtain mixed solution A4, and the mixed solution A4 was transferred to a 50 mL polytetrafluoroethylene reactor, reacted at 180 ° C for 24 h, cooled to room temperature, filtered and collected the precipitate, washed with deionized water and ethanol, and dried at 60 ° C under normal pressure to obtain a BiOBr / oyster shell composite photocatalyst.

[0048] Embodiment 3:

[0049] A BiOBr / oyster shell composite photocatalyst, which is different from Example 1 in that the molar ratio of BiOBr to oyster shell is controlled to be 2:1, is prepared by the following preparation method:

[0050] (1) Preparation of oyster shell powder:

[0051] Take discarded oyster shells as raw materials, wash them with water and then dry them, grind them in a ball mill at 500r / min for 1h, then put them in a tubular furnace, heat them to 700°C at a heating rate of 5°C / min, and calcine them for 6h to obtain oyster shell powder raw materials.

[0052] (2) Preparation of BiOBr / oyster shell composite photocatalyst:

[0053] 3mmol Bi(NO 3 ) 3 ·5H 2O was added to 20 mL of anhydrous ethanol and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A1; 3 mmol KBr was then added to 20 mL of anhydrous ethanol to be completely dissolved and ultrasonically dispersed at 200 W for 0.5 h to obtain dispersion A2; dispersion A2 was then added dropwise to dispersion A1, and after the addition was completed, stirring was continued at 1000 r / min for 0.5 h to obtain mixed solution A3, 1.5 mM oyster shell powder was added to the mixed solution A3, and ultrasonically dispersed at 200 W for 0.5 h again to obtain mixed solution A4, and the mixed solution A4 was transferred to a 50 mL polytetrafluoroethylene reactor, reacted at 180 ° C for 18 h, cooled to room temperature, filtered and collected the precipitate, washed with deionized water and ethanol, and dried at 60 ° C under normal pressure to obtain a BiOBr / oyster shell composite photocatalyst.

[0054] Application Example 1: Application of the BiOBr / oyster shell composite photocatalyst prepared in Example 1 to visible light photocatalytic degradation of methylene blue, a dye pollutant

[0055] 50mL 10 -5 MB solution of M was added to a 50 mL reactor, and 50 mg of BiOBr / oyster shell prepared in Example 1 was added. A 500 W xenon lamp was used as the light source to simulate sunlight, and a 420 nm filter was used to filter out ultraviolet light to ensure that the light received by the reaction was visible light. Stirring was carried out in the dark for 30 min to allow the catalyst and MB to reach an adsorption / desorption equilibrium state, and then the light source was turned on. Samples were taken at intervals during the reaction under dark and light conditions, and the supernatant was taken after centrifugation. The absorbance of the MB solution at a wavelength of 664 nm was measured on a UV-visible spectrophotometer to obtain the residual concentration of MB and calculate the degradation rate. The visible light degradation MB experiment of monomer BiOBr and monomer oyster shell was used as a control experiment (see Figure 3 ).

[0056] Depend on Figure 3 It can be seen that in the dark reaction, BiOBr / oyster shell showed good adsorption capacity for MB. Under visible light, the BiOBr / oyster shell composite photocatalyst showed good photocatalytic activity, and the photocatalytic performance was significantly better than that of monomer BiOBr and monomer oyster shell. The degradation rate of MB can reach 100% within 90 minutes of reaction time. Therefore, loading BiOBr with good visible light absorption performance and photocatalytic activity on oyster shell can effectively improve the adsorption performance of the material while effectively separating the photogenerated electrons and holes on the surface of the composite material, and improve the visible light absorption performance and specific surface area of ​​the composite material, thereby enhancing the visible light catalytic performance of the composite material. The BiOBr / oyster shell prepared in Example 2 and Example 3 can also achieve similar results as above.

[0057] Application Example 2: Application of the BiOBr / oyster shell composite photocatalyst prepared in Example 1 to visible light photocatalytic degradation of antibiotic ciprofloxacin pollutants

[0058] 50mL 10 -5 The CIP solution of 100 mL was added to a 50 mL reactor, and 50 mg of BiOBr / oyster shell prepared in Example 1 was added. A 500 W xenon lamp was used as the light source to simulate sunlight, and a 420 nm filter was used to filter out ultraviolet light to ensure that the light received by the reaction was visible light. Stirring was carried out in the dark for 30 min to allow the catalyst and CIP to reach an adsorption / desorption equilibrium state, and then the light source was turned on. Samples were taken at regular intervals during the reaction under dark and light conditions, and the supernatant was taken after centrifugation to measure the absorbance of the CIP solution at a wavelength of 278 nm on a UV-visible spectrophotometer to obtain the residual concentration of CIP and calculate the degradation rate (see Figure 4 ).

[0059] Depend on Figure 4 It can be seen that in the dark reaction, BiOBr / oyster shell showed good adsorption capacity for CIP. Under visible light, the BiOBr / oyster shell composite photocatalyst showed good photocatalytic activity, and the degradation rate of CIP could reach 100% within 90 minutes of photocatalytic reaction time. Therefore, loading BiOBr with good visible light absorption performance and photocatalytic activity on oyster shell can effectively improve the adsorption performance of the material while effectively separating the photogenerated electrons and holes on the surface of the composite material, and improve the visible light absorption performance and specific surface area of ​​the composite material, thereby enhancing the visible light catalytic performance of the composite material. The BiOBr / oyster shell prepared in Example 2 and Example 3 can also achieve similar results as above.

[0060] Application Example 3: Application of the BiOBr / oyster shell composite photocatalyst prepared in Example 1 to visible light photocatalytic degradation of dye malachite green pollutants

[0061] 50mL 10 -5 The MG solution of MG was added to a 50 mL reactor, and 50 mg of BiOBr / oyster shell prepared in Example 1 was added. A 500 W xenon lamp was used as the light source to simulate sunlight. A 420 nm filter was used to filter out ultraviolet light to ensure that the light received by the reaction was visible light. Stirring was carried out in the dark for 30 min to allow the catalyst and MG to reach an adsorption / desorption equilibrium state. Then the light source was turned on. Samples were taken at regular intervals during the reaction under dark and light conditions. After centrifugation, the supernatant was taken and the absorbance of the MG solution at a wavelength of 278 nm was measured on a UV-visible spectrophotometer to obtain the residual concentration of MG and calculate the degradation rate (see Figure 4 ).

[0062] Depend on Figure 4It can be seen that in the dark reaction, BiOBr / oyster shell showed good adsorption capacity for MG. Under visible light, the BiOBr / oyster shell composite photocatalyst showed good photocatalytic activity, and the degradation rate of MG could reach 100% within 90 minutes of photocatalytic reaction time. Therefore, loading BiOBr with good visible light absorption performance and photocatalytic activity on oyster shells can effectively improve the adsorption performance of the material while effectively separating the photogenerated electrons and holes on the surface of the composite material, and improve the visible light absorption performance and specific surface area of ​​the composite material, thereby enhancing the visible light catalytic performance of the composite material. The BiOBr / oyster shell prepared in Example 2 and Example 3 can also achieve similar results as above.

[0063] The above examples are only for illustrating the technical concept and technical features of the present invention, and cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A BiOBr / oyster shell composite photocatalyst, characterized in that: The raw materials for preparing the composite photocatalyst include BiOBr and oyster shells, wherein the molar ratio of BiOBr to oyster shells is 0.5-2:

1.

2. The composite photocatalyst according to claim 1, characterized in that The preparation method of the composite photocatalyst comprises the following steps: 1) Preparation of oyster shell powder: Taking oyster shell as raw material, washing, calcining and grinding are used to obtain oyster shell powder raw material; 2) Preparation of BiOBr / oyster shell composite photocatalyst: Bismuth nitrate pentahydrate Bi(NO3)3·5H2O is added to anhydrous ethanol and ultrasonically dispersed to obtain dispersion A1; potassium bromide KBr is then added to anhydrous ethanol and ultrasonically dispersed to obtain dispersion A2; dispersion A2 is added dropwise to dispersion A1, and stirring is continued after the dropwise addition is completed to obtain a mixed solution A3, oyster shell powder is added to the mixed solution A3, and ultrasonic stirring is performed again to mix evenly to obtain a mixed solution A4, the mixed solution A4 is subjected to a high temperature reaction, cooled to room temperature after the reaction, and a BiOBr / oyster shell composite photocatalyst is obtained through centrifugation, washing and drying.

3. The composite photocatalyst according to claim 2, characterized in that In the step 1), the grinding speed is 500 r / min and the grinding time is 1 h; the calcination condition is to increase the temperature to 700° C. at a heating rate of 5° C. / min and calcine for 3 to 6 h.

4. The composite photocatalyst according to claim 2, characterized in that The ultrasonic dispersion in step 2) has an ultrasonic frequency of 200W and an ultrasonic dispersion time of 0.5h.

5. The composite photocatalyst according to claim 2, characterized in that: The molar ratio of Bi(NO3)3·5H2O to KBr is 1:

1.

6. The composite photocatalyst according to claim 2, characterized in that The molar ratio of BiOBr to oyster shell powder is 0.5-2:

1.

7. The composite photocatalyst according to claim 2, characterized in that: In the step 2), the mixed solution A4 is transferred to a high-pressure reactor equipped with a polytetrafluoroethylene liner, and then the reactor is placed in an electric constant temperature blast drying oven and heat treated at 180° C. for 12 to 24 hours; after the reaction is completed, the reactor is cooled to room temperature, and the BiOBr / oyster shell composite photocatalyst is obtained by suction filtration, washing and drying.

8. Use of the composite photocatalyst according to claim 1 in degrading dyes or antibiotics.

9. A product for degrading dyes or antibiotics, characterized in that: The product contains the composite photocatalyst according to claim 1.

10. A method for degrading a dye or an antibiotic, characterized in that: The method described is to use the composite photocatalyst described in claim 1 to degrade dyes or antibiotics.

Citation Information

Cited By

  • Composite photocatalyst as well as preparation method and application thereof

    CN120169399A

  • Bismuth oxyhalide / biochar composite material as well as preparation method and application thereof

    CN120900667A